Changes to signal peptide and the level of transforming growth factor- β1 due to T869C polymorphism of TGF β1 associated with lupus renal fibrosis - Susianti, Hani; Handono, Kusworini; Purnomo, Basuki B; Widodo, Nashi; Gunawan, Atma; Kalim, Handono (SpringerPlus, 2014)
Lupus Nephritis (LN) is a serious manifestation of lupus that can lead to End Stage Renal Disease (ESRD). Fibrosis is the main feature of ESRD, and it is likely influenced by Transforming Growth Factor Beta1 (TGFβ1). The T869C gene polymorphism of TGFβ1 is assumed to change the signal peptide, that has potential to interfere the urine production and renal protein expression of TGFβ1. The influence of T869C gene polymorphism on TGFβ1 production and renal fibrosis was evaluated in this study. Subjects were 45 patients LN with renal fibrosis and 45 participants without renal fibrosis as control, that were recruited from 2011 to 2013. Their urinary TGFβ1 levels and TGFβ1 gene polymorphisms were examined. All lupus patients underwent renal biopsy to assess their protein expression of TGFβ1 in the renal tissue by immunohistochemistry and their renal fibrosis by morphometry and chronicity index. Changes in the signal peptide interaction with Signal Recognition Particle (SRP) and translocon of endoplasmic reticulum were analyzed by Bioinformatics. Levels of urinary and protein expression of TGFβ1 increased in the LN with renal fibrosis group. There were significant differences in levels of urinary TGFβ1 in T, C allele and TT, TC, CC genotypes between case and control groups. Furthermore, patients with C allele are 3.86 times more at risk of renal fibrosis than T allele. The C allele encodes proline, which stabilizes the interaction of the TGFβ1 signal peptide with SRP and translocon, resulting in elevation of TGFβ1 secretion. Our results indicated that T869C gene polymorphism of TGFβ1 changes the signal peptide, that contributes to the production of urinary TGFβ1 and affects renal fibrosis in lupus nephritis.